Novel "open-sorption pipe" reactor for solar thermal energy storage. (1st August 2016) - Aydin, Devrim; Casey, Sean P.; Chen, Xiangjie; Riffat, Saffa
Highlights: A novel 'open sorption pipe' heat storage was experimentally investigated. Effect of absolute moisture levels on heat storage performance was analyzed. Hygrothermal-cyclic performances of Zeolite 13X and vermiculite–calcium chloride were compared. Vermiculite–calcium chloride has more durable performance than Zeolite at 80 °C regeneration temperature. Sorption pipe system using vermiculite–calcium chloride provides energy storage density of 290 kW h/m 3 . Abstract: In the last decade sorption heat storage systems are gaining attention due to their high energy storage density and long term heat storage potential. Sorption reactor development is vital for future progress of these systems however little has done on this topic. In this study, a novel sorption pipe reactor for solar thermal energy storage is developed and experimentally investigated to fulfill this gap. The modular heat storage system consists of sorption pipe units with an internal perforated diffuser pipe network and the sorption material filled in between. Vermiculite–calcium chloride composite material was employed as the sorbent in the reactor and its thermal performance was investigated under different inlet air humidity levels. It was found that, a fourfold increase of absolute humidity difference of air led to approximately 2.3 times boost in average power output from 313 W to 730 W and an 8.8 times boost of average exergy from 4.8 W to 42.3 W. According to the testing results, each of three sorption pipes can provide an average air temperature lift of 24.1 °C over 20 h corresponding to a system total energy storage capacity of 25.5 kW h and energy storage density of 290 kW h/m 3 . Within the study, vermiculite–calcium chloride performance was also compared with the widely investigated Zeolite 13X. Vermiculite–calcium chloride showed a good cyclic ability at regeneration temperature of 80 °C with a steadier thermal performance than Zeolite. Energetic and exergetic cyclic efficiencies varied in the range of 0.69 → 0.61 and 0.21 → 0.14 in the cycles performed with vermiculite–calcium chloride whilst energetic and exergetic cyclic efficiencies of Zeolite testing were between 0.72 → 0.48 and 0.25 → 0.06.